Investigation of Neurokinin‐1 Receptor Antagonism as a Novel Treatment for Chronic Bronchitis in Dogs - M. Grobman; C. Reinero (Journal of Veterinary Internal Medicine, 2016)
Background Canine chronic bronchitis (CCB) results in cough lasting ≥2 months and airway inflammation. Adverse effects include risk of secondary infection associated with lifelong corticosteroid administration and prompt investigation into alternative therapies. Neurogenic pathways mediated by tachykinins that bind neurokinin (NK) 1 receptors may induce cough and airway inflammation. Maropitant, a NK‐1 receptor antagonist, has been advocated for treatment of CCB based on anecdotal improvement, but without scientific evidence. Hypothesis/Objectives Maropitant will blunt clinical signs and airway inflammation associated with CCB. Animals Client‐owned dogs (n = 8) with cough >2 months, thoracic radiographic evidence of airway disease and sterile airway inflammation (>7% non‐degenerate neutrophils, >7% eosinophils or both) on bronchoalveolar lavage (BAL) enrolled. Methods Maropitant (2 mg/kg) administered q48h for 14 days. Study endpoints included client perception of clinical signs (surveys at baseline and 14 days, and visual analogue scale [VAS] at baseline, 7, and 14 days), and BAL % neutrophils and eosinophils (baseline and 14 days). One‐way repeated measures ANOVA (VAS) and Wilcoxon‐signed rank‐sum tests (BAL cells, cough frequency) used with P < .05 considered significant. Results Maropitant significantly decreased cough frequency (P < .001) and VAS scores (P = .005). No differences in BAL % neutrophils or % eosinophils noted with treatment (P = .279 and P = .382, respectively). Conclusions and Clinical Importance Preliminary results suggest that although maropitant may have antitussive properties leading to perceived clinical improvement, its failure to diminish airway inflammation makes it unsuitable for treatment of CCB. Future studies could evaluate maropitant as a cough suppressant for other respiratory disorders in dogs.